"Mojster besede" za tretje tisočletje - Dović, Marijan (Jezik in slovstvo, 2018)
The article presents the new principal exhibition entitled "Župančič - A Master of Words", which was set up as part of the renovation of the Oton Župančič Memorial House in Vinica (2014-2015). Dedicated to Oton Župančič (1878-1949), one of the most important Slovenian poets and translators, the exhibition was set up by literary historian Marijan Dović and architect Jurij Kocuvan. It seeks to employ new approaches, media and technology to present Župančič's versatile literary mastery to various types of visitors, from children to connoisseurs. The visitor is guided through three thematic sections: "Children's Poetry and Bela Krajina", "Župančič's Drawing Room" and "Life and Work". Among the achievements of the new layout are the fresh audio interpretations of Župančič's poems, a new documentary film, an attractive audio and video design, and an outdoor playground that includes a beehive with Župančič's famous riddles. The exhibition is set up bilingually (in Slovenian and English) and is thus available to foreigners for the first time.
Keywords: Bela krajina; kanonizacija; literarni muzeji; moderna; razstave; rojstne hiše; slovenska književnost; slovenski pesniki; slovenski prevajalci; spomeniki; Vinica; Župančič, Oton